Flexibilité des gestes didactiques de métier en situation d’enseignement de l’éducation physique et sportive - Fabienne Brière; Marie-Paule Poggi; Gilles Marrot (Éducation et Socialisation)
The multi-dimensionalization of professional gestures questions the manifestations and foundations of their adjustment in context. Centred on three studies conducted in physical education and sport, the analysis of teachers' "professional didactic gestures" articulates approaches from didactics, the clinic of activity and sociology. This anchoring aims at examining the teacher's action in the light of the interactive processes of knowledge construction with the students, of the dilemmas experienced and of the contextual elements internal or external to the situation. The results show that the teachers' " professional didactic gestures " are constructed and adjusted in the interaction with the pupils by the resolution of dilemmas between a didactic déjà-là, a dispositional déjà-là and the present situation. The strong malleability of the gestures at the intersection of various contextual influences opens up the potential for the development of teachers' power to act.